Outbreak [large type] - Bunn, T. Davis, 1952- (Center Point Large Print, 2019)
"When sea currents shift, the red algae along the West African coast vanishes and the mysterious deaths stop. Professor Theo Bishop and biological researcher Avery Madison know the danger hasn't passed but changed locations and headed toward America. But everywhere they turn, powerful interests are determined to silence all credible evidence of the impending biological disaster"--